ECOTOURISM DEVELOPMENT OF SNORKELING AND DIVING ACTIVITY TOWARD CORAL REEF HABITATS IN THE LEMUKUTAN ISLAND OF BENGKAYANG REGENCY - Rudianto, Arif; Dewi, Yohana S. K; Burhanuddin, Burhanuddin (Jurusan Perikanan dan Kelautan, 2020)
Lemukutan Island has the potential of coral reefs to be developed into snorkeling and diving destinations. This study aims to (1) Analyze the suitability and carrying capacity of Lemukutan Island Conservation area in the development of snorkeling and diving ecotourism; (2) Formulate a strategy for developing Snorkeling and diving ecotourism in Lemukutan Island. Primary data collection with field observations and structured interviews to 30 respondents on Lemukutan Island. Secondary data is collected by various libraries and related. Based on results of the study, Lemukutan Island's coral reef ecosystem for the purpose of snorkeling and diving tourism was in the appropriate category (S2) with an IKW value of 76.8% and 68.86%. While the Ecological Carrying Capacity of each Â± 6,139 people / day and Â± 1,008 people / day. Based on the results of the SWOT analysis obtained alternatif strategies (1) Management and utilization of coral reefs optimally by taking into account the sustainability; (2) Increased access to Lemukutan islands, such as speed boats and timely departures; (3) Adding snorkeling and diving equipment, and improving resort services; (4) Arrangement of land and sea space in accordance with its designation so that marine resources can be sustainable; (5) Packaging of unique and environmentally based snorkeling and diving tours; (6) Increasing promotion through digital technology and promotion through tourism events to build partnership networks; (7) Improving skills for the community to open up alternative opportunities for new jobs; (8) Disseminating the importance of protecting coral reefs and making rules for snorkeling and diving tours